2016
DOI: 10.1515/rjdnmd-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Type 2 Diabetes Mellitus Risk (Assessed by Findrisc Score) is Associated with Subclinical Atherosclerotic Markers in Asymptomatic Adult Population

Abstract: Background and Aims. Risk score questionnaires for the screening of type 2 diabetes mellitus (DM) present high accuracy, especially the Finnish Diabetes Risk Score (FINDRISC IMT (r=0.24, p=0.01), PWV (r=0.26, p=0.008) or LVMI (r=0.23, p=0.01)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…T2DM is a threat to public health worldwide in view of its epidemic nature and effect on a number of health outcomes [ 16 ]. T2DM increases the risk of developing atherosclerosis [ 17 ], dyslipidemia [ 18 ], and hypertension [ 19 ], all of which are leading causes of death in both developed and developing countries. Owing to a rapidly changing lifestyle, the scale of this epidemic is of similar proportions in Jordan [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a threat to public health worldwide in view of its epidemic nature and effect on a number of health outcomes [ 16 ]. T2DM increases the risk of developing atherosclerosis [ 17 ], dyslipidemia [ 18 ], and hypertension [ 19 ], all of which are leading causes of death in both developed and developing countries. Owing to a rapidly changing lifestyle, the scale of this epidemic is of similar proportions in Jordan [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has however not known to be used in younger population in Africa. Reports from other studies indicated much higher age of 35-75 years of age (14)(15)(16)(17).…”
mentioning
confidence: 93%